Evaluation of graphite furnace and hydride generation atomic absorption spectrometry for trace analysis of arsenic in natural herbal medicine - Khalid, Reem S.; Helal Uddin, A.B.M.; Alaama, Mohammed; Abbas, S.A. (2016)
Introduction: Arsenic is a hazardous element that occurs in trace amounts in various environmental samples including natural products. The growing demand of such products for medical purposes imposes their safety and efficacy. Hydride generation atomic absorption spectrometry (HGAAS) is generally applied for trace analysis of arsenic in various matrices. However, such technique is tedious and involves hazardous materials. Graphite furnace atomic absorption spectrometry (GFAAS) has been used for metals measurements at trace concentration levels after reducing the interference problems by improving the background correction systems. This study aims to evaluate the adequacy of GFAAS as an alternative method to HGAAS for arsenic determination in natural herbal medicinal products by comparing the level accuracy and precision between the two methods. Method: The comparison was performed using three different real herbal medicine samples namely A, B and C spiked with known concentration of arsenic standard solution prior to microwave assisted acid digestion. Arsenic was detected with GFAAS and HGAAS. Results: Average recoveries of samples A, B and C using HGAAS and GFAAS were (89.3, 91.1 and 91.4) % and (91.7, 93.0 and 91.8) % respectively. The data was statically evaluated by independent samples t-test using Statistical Package for the Social Sciences (SPSS) and no significant effect was observed between both techniques. The limits of detection and the limit of quantification for HGAAS and GFAAS were (0.11- 1.17) and (0.12-1.2) ppb respectively. The relative standard deviation which represented the precision of the techniques was observed as (4.8, 2.58 and 5.5) % and (5.5, 5.7 and 1.99) % for samples A, B and C using HGAAS and GFAAS techniques respectively. The accuracy of both techniques was checked by the analysis of standard reference material 1515 Apple Leaves (SRM) from NIST. The percentage recoveries of arsenic were observed as 98 % and 102 % for GFAAS and HGAAS respectively. Both techniques showed convergent results in term of accuracy and repeatability. Conclusion: Subsequently GFAAS is recommended as a suitable, simple and less hazardous method for arsenic detection in natural herbal products.